An Analysis of Students' Errors in Using Simple Past Tense in Writing Recount Text at Senior High School Indramayu - Maulana Subagio; Indra Yoga Prawiro (National Conference on Language, Education, and Technology Proceeding, 2022)
Writing is one of the skills in English which is quite difficult to master because writing is a thinking activity or thought process that we put into the form of text or sentences. The definition is also supported by Harris (2014), who stated that writing is an activity of thinking to find or put ideas, concepts, and feelings that are expressed through writing in the form of sentences or paragraphs with the aim of readers understanding the intent and purpose of the author. This research was conducted to find out the errors that appeared in students' writing, especially in recount text. This research was carried out using a qualitative method which used document instruments from the results of students' writing on recount texts. Then, from the results of the documents written by the students, the researchers examined them to find out what errors often appeared in student writing, especially in recount texts. The results of this study show that errors in students' writing include omission, addition, misformation, and misordering. Then the results of this study also show that the most frequent errors in student writing are misformation with a total of 177 errors, the second is misordering errors with a total of 17, the third is omission errors with a total of 8, and the last is addition errors with a total of 4. The results of this study provide significant results for teachers and especially students. A significant research result for teachers is being able to provide evaluations of their teaching methods to students to provide more effective methods. Then the results of this study provide evaluations to students on how they do something, especially in writing activities.